Building an implementation framework to address unmet contraceptive care needs in a carceral setting: a systematic review - Douglas Routh; Rebecca Simmons; Jessica Sanders; Alexandra Gero; Hannah Aanderud Tanner; David K. Turok (BMC, 2023)
Abstract Background The provision of contraceptive care for incarcerated individuals has been largely inconsistent and has contributed to, at best, inadequate care, and at worst reproductive abuses, violence, and coercion. While previous research has identified strategies to remedy known issues, to date, very few recommendations have been implemented across the carceral system. To address this, we conducted a systematic review of policy and practice recommendations to improve contraceptive care to reproductive-aged, incarcerated individuals in the United States. Methods We conducted this systematic review utilizing the Joanna Briggs Institute methodology and framed it within the National Implementation Research Network's (NIRN) Exploration stage. We searched PubMed, PSYCInfo, SCOPUS, ProQuest, Web of Science, MedLine, Social Science Citation Index and reference sections of included materials. Basic study information, explicitly stated policy and practice recommendations, and discussions and conclusions that subtly provide recommendations were extracted in full text. We utilized a thematic analysis approach to analyze the extracted text. Results A total of 45 materials met the inclusion criteria. Seven overarching themes were identified: 1) policy changes needed to implement care; 2) need for contraceptive care in carceral systems; 3) justice agency barriers regarding contraceptive care provision; 4) policy barriers to contraceptive access; 5) funding strategies to improve care; 6) patient preferences for contraceptive care delivery; and 7) healthcare provider knowledge regarding contraceptive care. The seven themes identified shed light on the need for, gaps, barriers, and facilitators of current contraceptive care provision to incarcerated individuals. Conclusion This systematic review accomplished two goals of NIRN's Exploration stage. First, the compiled evidence identified a clear need for change regarding policies and practices pertaining to contraceptive care provision to incarcerated individuals in the United States. Second, our findings identified several evidence-based solutions supported both by research and professional healthcare organizations to address the identified need for change. This study provides an initial blueprint for correctional agencies to implement the necessary changes for improving contraceptive care provision to incarcerated populations. The correctional system is in a unique position to deliver much-needed care, which would result in many potential benefits to the individuals, correctional system, and community at large.